1571 Lower Limb Immobilisation And VTE Prophylaxis Risk Assessment: A Quality Improvement Project. (12th October 2021) - Potter, M
Abstract: Introduction: Temporary cast immobilisation of the lower limb following injury is associated with a 2-3% risk of DVT. NICE guidelines recommend considering pharmacological thromboprophylaxis for those with lower limb immobilisation where VTE risk outweighs bleeding risk. The aim of this quality improvement project was to improve compliance with VTE risk assessment in patients discharged from the Emergency Department (ED) with lower limb immobilisation. Method: Baseline data on completion of VTE risk assessment forms was collected retrospectively on all patients discharged from ED in lower limb boots and casts over a 3-week period. Cycle 1 included the introduction of a VTE section on the virtual fracture clinic booking form. Cycle 2 included displaying posters around the ED and placing forms inside walker boots. Data was collected following a 3-week period for each cycle. Results: The baseline audit showed 45% compliance with completion of VTE risk assessment forms. Cycle 1 showed a significant increase in compliance, to 72%. A further modest increase in compliance was seen in Cycle 2, with 78% of VTE risk assessment forms completed. Conclusions: Baseline compliance with VTE risk assessment for lower limb immobilisation was suboptimal. Integration of risk assessment into the virtual fracture booking form significantly improved compliance. This intervention is to be continued long-term at Harrogate District Hospital.